Neutrophils modulate post-thrombotic vein wall remodeling but not thrombus neovascularization - Henke, Peter K.; Varma, Manu R.; Deatrick, K. Barry; Dewyer, Nicholas A.; Lynch, Erin M.; Moore, Andrea J.; Dubay, Derek A.; Sukheepod, Pasu; Pearce, Charles G.; Upchurch, Gilbert R., Jr.; Kunkel, Steven L.; Franz, Michael G.; Wakefield, Thomas W. (Thrombosis and Haemostasis, 2006)
Early deep venous thrombosis (DVT) resolution is associated with neutrophil (PMN) influx. This study examined the role of PMNs in thrombus neovascularization and vein wall injury after DVT. A rat model of DVT by inferior vena cava (IVC) ligation was performed with control serum or rabbit anti-rat PMN serum administered perioperatively with sacrifice at 2 and 7 days. At 2 days, neutropenic rats had 1.6-fold larger thrombi (P = .04) and 1.4-fold higher femoral venous pressures by water manometry (P = .008) but no difference in thrombus neovascularization was observed. By7 days, DVT sizes were similar, but vein wall injury persisted in the neutropenic rats with a 2.0-fold increase in vein wall stiffness by microtensiometry (P< .05), as well asa 1.2-fold increased thickness (P = .04). Collagen and profibrotic growth factors were significantly increased in neutropenic IVC at7 days (all P< .05).Vein wall and intrathrombus uPA by Western immunoblotting, and intrathrombus MMP-9 gelatinase activity were significantly less in neutropenic rats than controls (P < .001). Conversely, MMP-2 was significantly elevated in neutropenic IVC at 2 days after DVT. However, neutropenia induced 24 hours after DVT formation resulted in no significant increase in vein wall stiffness or collagen levels at 7 days, despite 1.4-fold larger thrombi (P < .05). These data suggest a critical early role for PMN in post DVT vein wall remodeling.
Keywords: Animal models; tissue remodelling; leukocyte function / activation; deep vein thrombosis